Analisis Aktivitas Media Relation Dalam Model Public Relations (Studi Kasus Pada Biro Humas Universitas Teknologi Sumbawa) - Lisa Rosalina; M. Syukron Anshori (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
The development of social media as part of new media encourages public relations practitioners to realize the importance of media in shaping the positive image of an institution. This encourages the institution to establish good relations with the media through special activities called media relations. Based on the previous description, the researcher is interested in further studying media relations activities in the public relations model. This study aims to analyze media relations in public relations practices at the Public relations Bureau of the Sumbawa University of Technology by using descriptive qualitative research methods to obtain structured and in-depth information. The theory used is the theory of excellence which adapts four models of public relations communication as a basis for analysis, such as press agentry, public information, two-way asymmetrical, and two-way symmetrical. The results of the study show that the Public relations Bureau of the Sumbawa University of Technology applies a public relations model that focuses on providing quality information to the public through various communication channels, including social media. The implementation of public relations at the Public relations Bureau of the Sumbawa University of Technology, there are indications of the use of four public relations models. However, the two-way symmetrical model is considered the best one in achieving mutually beneficial relationships between organizations and the public.